Massachusetts Consortium for Innovative Education Assessments: Creating a grassroots accountability system to leverage state policy change - French, Dan (Education Policy Analysis Archives, 2018)
Standardized testing remains the predominant proficiency measure for students and schools, placing teacher and student focus on test-prep and lower order skills while maintaining achievement gaps that penalize underserved students. The Massachusetts Consortium for Innovative Assessment seeks to close this gap and change assessment measures on a state level by training teachers to become leaders in implementing student-centered performance assessments and encouraging state legislators to consider alternative, forward-thinking accountability systems.